The effect of comic strips used as class material in order to enhance the vocabulary of Readings and Conversation II students from English major with emphasis in Teaching, semester I 2017, afternoon shift at the Foreign Languages Department of the University of El Salvador - Ramos Aragón, Milagro Guadalupe; Argueta Chica, Marta Elisa (2024)
The topic of this research is: The effect of comic strips used as a class material in order to enhance the vocabulary of Readings and Conversation II students from English major with emphasis in Teaching, semester I 2017, afternoon shift at the Foreign Languages Department of the University of El Salvador. This project demonstrated how comic strips can be an effective material for English Teaching major students in order to reinforce their English language in the subject Readings and Conversation II, semester I, 2017. There are many fun ways in which students will get foreign language vocabulary. “Memorizing new words is a huge part of learning a new language”, “Reading is an essential activity because it is the best way to be exposed to a rich and wide vocabulary”. And at the same time it is important to understand the context given since that “context helps us comprehend when a word is used in formal language or informal language” (Magoosh, 2014, 12 Fun Ways to Learn and Remember New English Vocabulary). So this research starts considering comic strips as a class material that offers the students a great range of possibilities to enhance the vocabulary in the teaching and learning process of English as a foreign language. Besides, it is presented as a proposal material to be used in literature classes. For this reason, it will carry out a mix method research. The most appropriate instruments to explore this authentic printed material were checklist, note taking and closed - ended questionnaire. It was performed a mix method research since this kind of research method was so suitable in order to get information from the respondents of this study so it bore in mind the use of questionnaire or written interview making possible a better understanding of this research topic It analyzed the results of the use of comic strips with Readings and Conversation II students since it allowed the researchers to give some suggestions and make some proposals about the use of comic strips as an authentic printed material. On the other hand, the mix method research led to the staff member’s research to carry out an analysis about ludic material that the teacher is using regarding to English Readings and Conversation II subject. Thanks to this kind of method it was possible to collect data to give some suggestions and proposals about the suitability of the material used with educational aims. Briefly, the purpose of this study was to demonstrate the suitability of the already mentioned material as an educational tool in the course English Readings and Conversation II from English major in Teaching, afternoon shift at the Foreign Languages Department of the University of El Salvador, year 2017, that is why it was necessary to present a brief description of the material that the teachers use. In El Comic en la Clase de ELE: Una Propuesta Didáctico P5, Marina Alonso Abal demonstrated the suitability of comics as a teaching tool, without limiting it to a concrete age, reflecting on their potential addressing different aspects presented in comic strips, such as: the affective factor, the ludic component, the humor, the creativity, the interculturality, and the characteristics of iconic verb language which common point is its importance at the time to contribute definitely to the foreign language acquisition.